The macroeconometric model of the Bundesbank revisited - Thomas Haertel; Britta Hamburg; Vladimir Kusin (Deutsche Bundesbank, 2022)
The use of a semi-structural model as one of the workhorse tools for macroeconomic analysis and projections at the Bundesbank has a long-standing tradition. In an iterative projection process, the macroeconometric model's main task is to merge projections by Bundesbank experts for various areas of the economy and other information into a unifying framework in order to develop a consistent narrative on the outlook for the German economy. Besides this, the model is frequently used to perform simulation analyses both in the projection context and beyond. Its structure thus has to be broad enough to capture the key interdependencies within the macroeconomy whilst also including a sufficiently detailed setup. This paper summarises the model's main equation blocks, shows growth decompositions of key macro variables and presents selected simulation results in order to illustrate key transmission channels. The model has a traditional semi-structural character and is set in a national accounts framework. Most of its central behavioural equations follow an error-correction mechanism and are estimated individually based on quarterly data. One particular feature is the constant elasticity of substitution (CES) production technology with a two-level nested structure that integrates energy as a third input factor in addition to capital and labour. In the model's price block, behavioural equations for most deflators and HICP core inflation are jointly specified and estimated via a system approach. Moreover, the model contains a rich fiscal block.
Keywords: C30; E10; E17; E6; 330; Semi-structural model; Germany; macroeconomic forecasting; policy simulations